2011
DOI: 10.1063/1.3622630
|View full text |Cite
|
Sign up to set email alerts
|

Deuteration effects in the thermal conductivity of molecular glasses

Abstract: The thermal conductivity κ(T) of pure deuterated ethanol has been measured under its equilibrium vapor pressure in its orientationally-ordered crystal (T = 2 K -T m ), orientational glass and the glass state (T = 2 K -T g , T g is the glass transition temperature) solid phases. The temperature dependence of the conductivity is well described by a sum of two contributions: κ(T) = κ I (T) + κ II (T), where κ I (T) account for the heat transport by acoustic phonons and κ II (T) for the heat transfer by localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…A rough estimate of the mass effect yields κ ∝ M −1/2 . These results however contrast with previous studies on other materials which have shown that the increase in molecular mass decreases the rate of phonon scattering [23,24]. The typical bell-like shape for κ(T ) for ordered phases in such a log-log plot is clearly observed and thus, after the maximum, κ(T ) decreases with temperature.…”
Section: Data Analysis and Resultscontrasting
confidence: 55%
“…A rough estimate of the mass effect yields κ ∝ M −1/2 . These results however contrast with previous studies on other materials which have shown that the increase in molecular mass decreases the rate of phonon scattering [23,24]. The typical bell-like shape for κ(T ) for ordered phases in such a log-log plot is clearly observed and thus, after the maximum, κ(T ) decreases with temperature.…”
Section: Data Analysis and Resultscontrasting
confidence: 55%
“…S7). Thus, the effect of H/D isotope substitution on the glass transition of water (ΔT g ≈10 K) is significantly stronger than in other hydrogenbonding materials such as ethanol (ΔT g ≈ 0 K) (12,46), PG (ΔT g ≈ 0.1 K), and glycerol (ΔT g ≈ 0.4 K) (45).…”
Section: Details Of Dielectric Spectroscopy Measurementsmentioning
confidence: 99%
“…It was demonstrated with protonated ethanol [1] that the thermal conductivity curves of orientational and structural glasses having basically different molecular disorderings were unexpectedly close in value and temperature dependence. This finding was then confirmed in the investigation of the thermal conductivity of deuterated ethanol [2]. The behavior of the thermal conductivity of ethanol glasses suggests that the acoustic phonon scattering in glasses is caused mainly by the orientational molecular disor- der rather than the structural one.…”
Section: Introductionmentioning
confidence: 65%
“…Of special interest are the temperature dependences of the thermal conductivity κ(T ) of these objects. They deviate from the corresponding dependences typical of orientationally-ordered molecular crystals: there is no phonon maximum in most of them [1][2][3]. The dependences κ(T ) also differ from those typically observed in structural glasses; they have no plateau and do not increase with a rising temperature [4].…”
Section: Introductionmentioning
confidence: 99%